Perception and Reinterpretation of English Song Lyrics by Native Speakers of Japanese: A Case Study of Samples From the TV-Show Soramimi-Hour - Scherling, Johannes; Kornder, Lisa; Kelly, Niamh (Frontiers in Communication, 2022)
Cross-linguistic mondegreens occur when foreign song lyrics are misperceived and reinterpreted in the listener’s native language. In Japan, such humorous reinterpretations of non-native song lyrics are known as soramimi (空耳, ‘mishearing’). Word plays of this kind do not only have an entertaining character for listeners, but they also offer a valuable source to identify and describe potential phonological processes which can be observed in native Japanese listeners’ adaptations of English song lyrics into Japanese. We hypothesized that the reinterpretation of English song lyrics by Japanese listeners is a result of the perception of non-native auditory input through the first language Japanese phonological and morphological system. That is, misperceptions do not occur arbitrarily, but are governed by the phonological and morpho-phonological rules of the listener’s first language system. To test this hypothesis, we examined a corpus containing 60 English-Japanese mondegreens taken from the Japanese TV-show Soramimi Awā (Soramimi Hour). Results confirmed our hypothesis: The Japanese adaptations were observed to follow different phonological processes which aimed to subject the non-native auditory input to the phonological rules of Japanese.